Mixed Nodule Infection in Sinorhizobium meliloti–Medicago sativa Symbiosis Suggest the Presence of Cheating Behavior - Checcucci, Alice; Azzarello, Elisa; Bazzicalupo, Marco; Galardini, Marco; Lagomarsino, Alessandra; Mancuso, Stefano; Marti, Lucia; Marzano, Maria C.; Mocali, Stefano; Squartini, Andrea; Zanardo, Marina; Mengoni, Alessio (Frontiers in Plant Science, 2016)
In the symbiosis between rhizobia and legumes, host plants can form symbiotic root nodules with multiple rhizobial strains, potentially showing different symbiotic performances in nitrogen fixation. Here, we investigated the presence of mixed nodules, containing rhizobia with different degrees of mutualisms, and evaluate their relative fitness in the Sinorhizobium meliloti–Medicago sativa model symbiosis. We used three S. meliloti strains, the mutualist strains Rm1021 and BL225C and the non-mutualist AK83. We performed competition experiments involving both in vitro and in vivo symbiotic assays with M. sativa host plants. We show the occurrence of a high number (from 27 to 100%) of mixed nodules with no negative effect on both nitrogen fixation and plant growth. The estimation of the relative fitness as non-mutualist/mutualist ratios in single nodules shows that in some nodules the non-mutualist strain efficiently colonized root nodules along with the mutualist ones. In conclusion, we can support the hypothesis that in S. meliloti–M. sativa symbiosis mixed nodules are formed and allow non-mutualist or less-mutualist bacterial partners to be less or not sanctioned by the host plant, hence allowing a potential form of cheating behavior to be present in the nitrogen fixing symbiosis.